Lipid and sterol gene sequence variation in autism and correlates with neurodevelopmental status: A pilot study. Issue 6 (September 2015) - Hall, Trevor A.; Steiner, Robert D.; Wright, Hollis; Wilmot, Beth; Roullet, Jean-Baptiste; Peters, Meaghan; Harris, Michael
Abstract: Objective: Research has uncovered potential links between lipid and sterol metabolism and autism spectrum disorder (ASD). We worked to characterize genetic sequence variants in lipid/sterol related genes in children affected with ASD to investigate the association between lipid/sterol gene sequence variation and neurodevelopmental phenotype that could identify new etiologies for ASD and eventually aid to focus intervention strategies. Design and methods: Children with confirmed ASD were recruited from a regional academic health center. Participants included 24 children (20 male and 4 female) between the ages of 40 to 81 months ( M =60 months). Several neurodevelopmental measures were administered which provided an assessment of neurodevelopmental functional status. We applied our exome sequencing workflow to perform alignment to the Human Reference Sequence (build 37) base calling for every base pair in the reads that align to the reference sequence QC evaluation of the annotation of all genetic variants different from the reference sequence using dbSNP and the 1000 Genomes databases. We investigated whether novel variants identified were related to neurodevelopmental functioning. Results and conclusions: Variants occurred in 355 total genomic positions, 53 of which were not previously annotated as variant positions in either dbSNP or the 1000 Genomes Project׳s variant annotation. Of these 355 variants, 169 were nonsynonymous (31 were novel). The total number of variants observed in the exons of captured regions of an individual participant ranged from 88 to 117; novel variants ranged from four to 10 per participant, while nonsynonymous variants ranged from 36 and 51 per participant. The total number of nonsynonymous variants per subject was significantly associated with neurodevelopmental function. Further, several genes involved in sterol and lipid metabolism including NPC1, DHCR24 and others that when mutated cause diseases with ASD characteristics, were associated with ASD in Network analysis. Altogether, the findings suggest that nonsynonymous variants in lipid/sterol related genes may be a biological marker of neurodevelopment status in ASD. Results support an association between lipid and sterol metabolism and ASD and suggest the need for further research attempting to elucidate the mechanisms behind the association and the etiology and neurodevelopmental effects of ASD. Focal points: Bedside Understanding the association between genetics and metabolism and ASD will contribute to the scientific understanding of complex neurodevelopmental disorders. Continued study into the association between lipid and sterol genes and ASD may lead to new novel and effective treatment options for ASD. Benchside A large number of genetic sequence variations are associated with ASD. Additional research is still needed to determine which associations contribute to various subtypes of ASD presentations, and to elucidate the mechanisms behind the observed association. Industry The discovery of new genetically influenced ASD subtypes may lead to the development of new novel and effective treatment options for ASD. Community The development of new novel and effective treatment options for ASD will have a great impact on the quality of life of those impacted by ASD. Regulatory agencies Since the development of new novel and effective treatment options for ASD based on genetic substrates of the condition needs extensive support from the authorities for success in clinical translation, ongoing financial investments will be necessary to translate the research in the lab to the bedside. The governmental support can also help to minimize the associated costs of treating ASD overtime.